PENDIDIKAN PEREMPUAN: DEWI SARTIKA DAN SEKOLAH KAUTAMAAN ISTRI 1904-1942 - Indra Rahmat Jatnika (KARMAWIBANGGA Historical Studies Journal, 2025)
Education for indigenous women during the Dutch Colonial era was still a difficult thing to do. At that time, women were constrained by the culture of society that women were considered not to have to or even did not need to attend school, especially for the lower middle class. Education for women is an interesting topic to study, therefore the purpose of this study is to determine the background of the establishment of the Kautamaan Istri school and its development in 1904-1942. The method used in this study is the literature study method. The research method used is the historical research method, starting from the heuristic stage, source verification, interpretation, and historiography. The results of this study are that Dewi Sartika's thoughts on education for women are influenced by her family background and the environment in which she lives. Dewi Sartika wants women to be useful for themselves, their families and society. Therefore, Dewi Sartika built the Kautamaan Istri School on January 16, 1904. Dewi Sartika believes that women must have knowledge, so that they do not depend on others, so through education for women, young women are directed to apply values ​​and norms according to applicable regulations. The curriculum taught at the Kautamaan Istri School includes cooking, washing, sweeping, taking care of the household as well as reading, writing and arithmetic. Because the purpose of this school is to prepare competent women to educate children and take care of the household.